SEJARAH KONSTITUSI DI INDONESIA (Dari Masa Ke Masa) - Pobela, Moh. Ramsliyanto (Jurnal GeoCivic, 2023)
Since the independence of Indonesia was proclaimed by Bung Karno on August 17 1945, there were four written constitutions or Basic Laws that have been existed they are, First; The period on 18 August to 27 December 1949 (1945 Constitution), Second; The period onÂ  27 December1949-17 August 1950 (1949 RIS Constitution), Third; The period on 17 August 1950 to 5 July 1959 (UUDS 1950), Fourth; Period on 5 July 1959 until now (1949 Constitution of the Republic of Indonesia). Constitutions and basic laws have different limitation, even though both of them refer to the meaning of basic law. The constitution has a broader meaning, it means that the constitution includes all regulations, both written and unwritten, however the basic law is the part of the written constitution. The constitution becomes the main and principal design of the entire system of rules as a common guideline in the lives of citizens in a country, the whole of them create legal system like a "religion" (constitutional faith) or civil religion for every citizen. Therefore, the laws and constitution of a country must be something that lives in the practice of state life. From here we can believe that the principle of the rule of law or the principle of supremacy of law can truly be realized.Keyword : History, Constitution, Indonesian.